TRADISI RITUAL BUKA LUWUR (Sebuah Media Nilai-nilai Islam dan Sosial Masyarakat Kudus) Ritual Tradition Buka Luwur (A Media of Islamic and Social Values in Kudus’ Society) - Ulin Nuha (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
Buka Luwur is one the traditions practiced in Kudus Central Java. This ceremony plays as a media for disseminating religious and social values to society. The Aims of this research are to study Buka Luwur ritual as a media of disseminating religious and cultural values, and to know its functions and factors that create the tradition. This research uses sociological approach. Data was collected using interviews and interpretive analysis. There are four aspects found from this study as follows; Firstly, Buka Luwur is a religious ceremony for commemorating the death of Sunan Kudus and as a form of pilgrimage. Secondly, this tradition contains good values that need to be institutionalized and transmitted to next generations. Thirdly, Muslims’ understanding on Qur’an is interrelated with their local culture and the influence from outside Islam. Fourthly, the harmony in society will work well on condition that it is supported by living tradition. The tradition of Buka Luwur plays as an element to unify groups in society, and it can be element for social cohesion, to solidify the believe in supernatural power, to protect balance and harmony of society from time to time